2012
DOI: 10.1021/ma3019359
|View full text |Cite
|
Sign up to set email alerts
|

Interplay of Phase Separation and Thermoreversible Gelation in Aqueous Methylcellulose Solutions

Abstract: Rheology and turbidity measurements were performed under similar thermal histories to probe the relationship between thermoreversible gelation and phase separation for a set of three methylcellulose (MC) materials with similar degrees of substitution (DS) and contrasting molecular weights after hydration in cold water. Frequency-independent loss tangents were used to identify the gel point (T gel ) in MC solutions well over the chain overlap concentration (c ≥ 10c*). Transmittance of 633 nm laser light through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
183
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(206 citation statements)
references
References 41 publications
(107 reference statements)
21
183
1
Order By: Relevance
“…Through another methodology, most researchers focus on using instrumental techniques to elucidate the thermodynamic mechanisms involved in the sol-gel transition and/or phase separation. These techniques include turbidity, laser light scattering, viscometry, rheology, differential scanning calorimetry (Arvidson et al 2012;Fairclough et al 2012;Lu et al 2002;Xu et al 2004), and recently by mid/near infrared spectroscopy (Jing and Wu 2013), small-angle neutron scattering combined with cryogenic transmission electron microscopy (cryo-TEM) (Lott et al 2013a, b;McAllister et al 2015). These studies demonstrate that the sol-gel transition is a spinodal process (Takeshita et al 2010) or a nucleation and growth mechanism (Arvidson et al 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Through another methodology, most researchers focus on using instrumental techniques to elucidate the thermodynamic mechanisms involved in the sol-gel transition and/or phase separation. These techniques include turbidity, laser light scattering, viscometry, rheology, differential scanning calorimetry (Arvidson et al 2012;Fairclough et al 2012;Lu et al 2002;Xu et al 2004), and recently by mid/near infrared spectroscopy (Jing and Wu 2013), small-angle neutron scattering combined with cryogenic transmission electron microscopy (cryo-TEM) (Lott et al 2013a, b;McAllister et al 2015). These studies demonstrate that the sol-gel transition is a spinodal process (Takeshita et al 2010) or a nucleation and growth mechanism (Arvidson et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…These techniques include turbidity, laser light scattering, viscometry, rheology, differential scanning calorimetry (Arvidson et al 2012;Fairclough et al 2012;Lu et al 2002;Xu et al 2004), and recently by mid/near infrared spectroscopy (Jing and Wu 2013), small-angle neutron scattering combined with cryogenic transmission electron microscopy (cryo-TEM) (Lott et al 2013a, b;McAllister et al 2015). These studies demonstrate that the sol-gel transition is a spinodal process (Takeshita et al 2010) or a nucleation and growth mechanism (Arvidson et al 2012). The cryo-TEM even revealed that MC chains associate into nanofibrils with uniform diameter of 15 ± 2 nm in the MC gels, which clearly explains the formation of optically turbid gel or precipitation (Lott et al 2013a, b;McAllister et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was confirmed experimentally by rheological measurements that a nucleation and growth mechanism is also involved in the gelation of MC, as the gelation temperature depends on the heating rate [65].…”
Section: Colloidal Dissolution and Gelation As Processes Involved In mentioning
confidence: 93%
“…Because the gelation of MC hydrogels is a rate-dependent process, 18,19 simultaneous measurement is essential. Raman spectroscopy is a non-contact technique.…”
Section: Gelation Mechanism Of Methylcellulose Hydrogels Containing Pmentioning
confidence: 99%
“…The development of a fibrillar structure with increasing temperature correlates with the rheological and turbidity behavior. 18,19 The MC-PEG-water system forms a thermo-reversible gel during heating. We have investigated the water state and dynamic mechanical property of an MC-PEG-water system and reported that the memory of the gel state was maintained for three days after gelation at 277 K. The period of maintaining the memory of the gel state after gelation is in agreement with the strength of the PEG-water interaction.…”
Section: Introductionmentioning
confidence: 99%